2017
DOI: 10.21272/bel.1(4).49-57.2017
|View full text |Cite
|
Sign up to set email alerts
|

Public Policy for Corporate Social Responsibility and Governance for Sustainable Tourism Development in Greece

Abstract: Business innovation, employment generation, environmental sustainability and good governance were some of the fundamental issues that crisis highlighted in Greece as prerequisites for sustainable development. The tourism sector sustainability in parallel with environmental modernization competiveness and social welfare is a complicated and a non linear policy task. The sustainable development in European Union and member states such as Greece is crucial for 2020 and 2030. Moreover, it is essential for the tour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…In this case, enhancing sustainable tourism was related to the tourists' green awareness. In addition, the authors of [29][30][31][32], who investigated the Caribbean Region, Greece, and Armenia using questionnaires and statistical analysis, confirmed that social capital and the level of green awareness in a society influence sustainable tourism development.…”
Section: Literature Reviewmentioning
confidence: 87%
“…In this case, enhancing sustainable tourism was related to the tourists' green awareness. In addition, the authors of [29][30][31][32], who investigated the Caribbean Region, Greece, and Armenia using questionnaires and statistical analysis, confirmed that social capital and the level of green awareness in a society influence sustainable tourism development.…”
Section: Literature Reviewmentioning
confidence: 87%
“…A brief presentation for European Social Model is necessary at this point and its regional characteristics which are called social models in EU (Commission, 1994;Eurofound, 2011;European Economy News 2006;Kotroyannos, et al, 2013;Sapir, 2004). The social models had also a significant impact to CSR perceptions, public policy models and EU citizens approach in welfare issues, due to this institutional tradition (Taliouris, 2019; but also traditional policy topics education, employment and social security.…”
Section: Youth Education and Social Welfarementioning
confidence: 99%
“…Despite the fact that youth in EU and Greece pay attention on business sector responsible activities and entrepreneurship (EURES, 2023), policy experience indicates this strategy very useful but optimistic not only for EU (Commission, 2016) but also Greece (2017;. Business sector is an important stakeholder for social equity and European Social Model (Sapir, 2004;Taliouris, 2019; because contribute in employment increase and social inclusion. Although EU and its member states have a significant institutional tradition in social welfare and considered as one of the best places to live, political steps need to be taken in order to ensure youth capability to meet their own needs.…”
Section: Youth Education and Social Welfarementioning
confidence: 99%
“…The problem of increasing the energy efficiency level in Ukraine is one of the essential issues to ensure sustainable innovation development and the country's energy independence. Domestic and scientists from abroad (Pavlyk, 2020;Palienko, Lyulyov, Denysenko, 2017;Taliouris, Trihas, 2017;Molotok, 2020;Palienko, Lyulyov, 2018) pay great attention to the study of the impact of innovation and investment determinants on the development of energy efficiency of the national economy and how the level of energy efficiency of the country affects macroeconomic stability and competitiveness.. I.M. Mazur (Mazur, 2014), in his research, pays attention to the main problems of the development of energyefficient enterprises in the national economy of Ukraine, improving their energy security and maximizing their impact on the environment by increasing energy efficiency.…”
Section: Literature Reviewmentioning
confidence: 99%